Scar-Free Healing of Endometrium: Tissue-Specific Program of Stromal Cells and Its Induction by Soluble Factors Produced After Damage - Eremichev, Roman; Kulebyakina, Maria; Alexandrushkina, Nataliya; Nimiritsky, Peter; Basalova, Nataliya; Grigorieva, Olga; Egiazaryan, Mane; Dyikanov, Daniyar; Tkachuk, Vsevolod; Makarevich, Pavel (Frontiers in Cell and Developmental Biology, 2021)
Besides certain exceptions, healing of most tissues in the human body occurs via formation of scar tissue, rather than restoration of lost structures. After extensive acute injuries this phenomenon substantially limits the possibility of lost function recovery and in case of chronic injury it leads to pathological remodeling of organs affected. Managing outcomes of damaged tissue repair is one of the main objectives of regenerative medicine. The first priority for reaching it is comparative investigation of mechanisms responsible for complete restoration of damaged tissues and mechanisms of scarring. However, in human body tissues that undergo complete scar-free healing are scarce. The endometrium is a unique mucous membrane in the human body that heals without scarring after various injuries, as well as during each menstrual cycle (i.e. up to 400 times during a woman’s life). We hypothesized that absence of scarring during endometrial healing may be associated with tissue-specific features of its stromal cells or their microenvironment, since stromal cells transform into myofibroblasts – the main effector link of scarring. We found that during healing of the endometrium, soluble factors are formed that inhibit the transition of stromal cells into myofibroblasts. Without influence of these factors, the stromal cells of the endometrium undergo transformation into myofibroblasts after TGF-b1 treatment as well as the stromal cells from tissues that heal by scarring - skin or fat. However, unlike the latter, endometrial stromal cells organize ECM in a specific way and are not prone to formation of bulky connective tissue structures. Thus, we may suggest that tissue-specific features of endometrial stromal cells along with effects of soluble factors secreted in utero during menstruation ensure scar-free healing of human endometrium.